Dampak Tempat Pembuangan Akhir (TPA) terhadap Masyarakat di Sekitar TPA Air Dingin Kota Padang - Khoiruddin Al Amin; Deded Chandra (YASIN, 2024)
This research aims to determine 1) the community's response to the existence of a landfill, 2) the social impact of the existence of a landfill and 3) the economic impact of the existence of the Padang City Cold Water Landfill. This research was carried out using a quantitative method approach using descriptive percentage analysis techniques and T test analysis to obtain results on the impact of landfills. The results of this research show: 1) The public's response to the existence of the Padang City Cold Water Waste Final Disposal Site (TPA) is on average good for zoning ≤500 meters from the TPA, which shows that the community accepts the existence of the TPA. 2) Social impact: The community in Balai Gadang Subdistrict, Koto Tangah District, which is under 500 meters from the landfill, said they felt more than half of the social impact of the existence of the Air Cold Landfill. 3) Communities located below 500 meters and 500-1000 meters from the landfill experience more than half of the economic impact of the existence of the Cold Water Landfill in Balai Gadang Village, Koto Tangah District.